2018
DOI: 10.1017/s0022377818001289
|View full text |Cite
|
Sign up to set email alerts
|

Direct construction of optimized stellarator shapes. Part 1. Theory in cylindrical coordinates

Abstract: The confinement of guiding center trajectories in a stellarator is determined by the variation of the magnetic field strength B in Boozer coordinates (r, θ, ϕ), but B(r, θ, ϕ) depends on the flux surface shape in a complicated way. Here we derive equations relating B(r, θ, ϕ) in Boozer coordinates and the rotational transform to the shape of flux surfaces in cylindrical coordinates, using an expansion in distance from the magnetic axis. A related expansion was done by Garren and Boozer [Phys. Fluids B 3, 2805 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
137
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 67 publications
(138 citation statements)
references
References 20 publications
(62 reference statements)
1
137
0
Order By: Relevance
“…The leading-order field strength B 0 is approximately the toroidal flux divided by the cross-sectional area of the flux surfaces. Indeed, this interpretation of (A 21) is shown precisely in Landreman & Sengupta (2018). The area of the surfaces is primarily determined by the sin ϑ and cos ϑ modes of X and Y , which generate ellipses, and not by sin 2ϑ, cos 2ϑ, and independent-of-ϑ modes which distort and shift the ellipses but do not expand or contract them.…”
Section: )mentioning
confidence: 89%
See 2 more Smart Citations
“…The leading-order field strength B 0 is approximately the toroidal flux divided by the cross-sectional area of the flux surfaces. Indeed, this interpretation of (A 21) is shown precisely in Landreman & Sengupta (2018). The area of the surfaces is primarily determined by the sin ϑ and cos ϑ modes of X and Y , which generate ellipses, and not by sin 2ϑ, cos 2ϑ, and independent-of-ϑ modes which distort and shift the ellipses but do not expand or contract them.…”
Section: )mentioning
confidence: 89%
“…Since I(r) is proportional to the toroidal current inside the surface r, then I 0 = 0. From analyticity considerations near the axis (see appendix A of Landreman & Sengupta (2018)), the expansion coefficients have the form…”
Section: Near-axis Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using near-axis asymptotic expansions (Garren & Boozer 1991;Landreman & Sengupta 2018;, it has been shown that the QS constraint makes the MHD system overdetermined, and in general, such magnetic fields might not exist in a given volume. Lack of QS in a volume intrinsically deteriorates the confinement of α particles, and careful numerical optimization is required (Bader et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Renewed interest in stellarator design has sparked questions on the existence and accessibility of threedimensional magneto-hydrodynamic (MHD) equilibria with "good" nested flux-surfaces [1][2][3][4][5][6] . Several numerical tools exist to obtain three-dimensional MHD equilibria by means of variational principles [7][8][9] , initial value problems 10,11 , iterative methods 12,13 , metriplectic formulations 14 , analytic expansions around a given magnetic axis 15,16 . These methods aspire to produce and optimise the magnetic fields so that the field-lines lie on toroidally nested flux-surfaces 17,18 , which is the basis of plasma confinement in magnetic fusion devices such as tokamaks and stellarators 19 .…”
Section: Introductionmentioning
confidence: 99%